Whole-Genome Resequencing of Xiangxi Cattle Identifies Genomic Diversity and Selection Signatures - Luo, Xiaoyu; Li, Jianbo; Xiao, Chentong; Sun, Luyang; Xiang, Weixuan; Chen, Ningbo; Lei, Chuzhao; Lei, Hong; Long, Yun; Long, Ting; Suolang, Quji; Yi, Kangle (Frontiers in Genetics, 2022)
Understanding the genetic diversity in Xiangxi cattle may facilitate our efforts towards further breeding programs. Here we compared 23 Xiangxi cattle with 78 published genomes of 6 worldwide representative breeds to characterize the genomic variations of Xiangxi cattle. Basing on clustering models in population structure analysis, we displayed that Xiangxi cattle had a mutual genome ancestor with Chinese indicine, Indian indicine and East Asian taurine. Population genetic diversity analyzed by four methods (nucleotide diversity, inbreeding coefficient, linkage disequilibrium decay and runs of homozygosity), we found Xiangxi cattle had higher genomic diversity and weaker artificial selection compared with commercial breed cattle. Using the four methods (θπ, CLR, FST and XP-EHH) test, we explored positive selection regions harboring genes in Xiangxi cattle, which was related to reproduction, growth, meat quality, heat tolerance and immune response. Our finding revealed the sequence variations of Xiangxi cattle at the genome-wide level. These results provided a valuable genomic resource for genetic studies and breed protection in the future.